-16=-4(2x-8)

Simple and best practice solution for -16=-4(2x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=-4(2x-8) equation:


Simplifying
-16 = -4(2x + -8)

Reorder the terms:
-16 = -4(-8 + 2x)
-16 = (-8 * -4 + 2x * -4)
-16 = (32 + -8x)

Solving
-16 = 32 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-16 + 8x = 32 + -8x + 8x

Combine like terms: -8x + 8x = 0
-16 + 8x = 32 + 0
-16 + 8x = 32

Add '16' to each side of the equation.
-16 + 16 + 8x = 32 + 16

Combine like terms: -16 + 16 = 0
0 + 8x = 32 + 16
8x = 32 + 16

Combine like terms: 32 + 16 = 48
8x = 48

Divide each side by '8'.
x = 6

Simplifying
x = 6

See similar equations:

| 7x+4=6y+5 | | 6(2a)=3 | | 15x+12=7x-52 | | 9*8+10= | | 5(w-4)-8w=4 | | d+d+d=9 | | 17+7=a+8 | | 9*8-10= | | 2x-6=6x-14 | | 1.8Q-4.7-1.6Q=-0.8Q-4.1 | | 2236000-17740r=3500000 | | 8x+3-10x=-2(x-2)+x | | 34+5x=99 | | 5(w-4)-8=14 | | 0.6x-10=104x-14 | | 5=x^2-441 | | x+16(x-1)=7(3+x) | | 3+m=29 | | (2w^2+2w)+(9w^2+4w+3)= | | 5(x-3)+2k=41 | | 27+5s=189 | | (2w^2+2w)+(9w^3+4w+3)= | | -10x-10+3x=18 | | 39x+2=158 | | -2(8+2x)=-28 | | 4+8x=126 | | y-20=-42 | | 5x=8-12x+6 | | 25x+15=90 | | -5-3x=10 | | 3y+5=41 | | 2x-9+3x=9-x |

Equations solver categories